SOY MILK BEVERAGE DIVERSIFICATION WITH THE ADDITION OF DATE EXTRACT AS SUGAR SUBSTITUTE - Satria, Budi; Juanita, Juanita; Nilda, Cut; Hasni, Dian; Muzaifa, Murna (Universitas Syiah Kuala, 2023)
Most of the people in Neuhen village have a low income with the majority working irregularly or odd jobs, but there are also those who have home industry businesses such as soya bean milk drinks. The business has not developed well because the processing method is still very simple. This service activity aims to foster the soya milk drink business and diversify the product by adding date extract as a sugar substitute sweetener. The activities are reviewing how soy milk processing has been carried out by partners and seeing the tools used. The method of manufacturing soy date milk with date extract is then carried out. Experiments with date soy milk were conducted by adding date extract in various quantities, namely 25% and 50% of the total soy milk. The product is then randomly tested on individuals. People choose soy date milk that contains 25% dates, has the proper quantity of sweetness, and is not too foggy in color. It is intended that partners would manufacture soy date milk that meets food safety and appropriate criteria and can be consumed by everyone, including diabetics.